Bilateral thigh abscess due to rectal fistula: A rare case report with silent clinical presentation (Annals of Medical Research, 2023)
A 53-year-old male patient who underwent a rectal cancer operation nine years ago was evaluated with complaints of pain and swelling in the lateral thigh. Radiological imaging revealed abscess foci in the right thigh muscles. Surgical drainage and debridement were performed but developed recurrence. Contrast-enhanced abdominal tomography was performed due to a positive medical history and it was seen that an enterocutaneous fistula was formed from the anastomosis site of previous cancer surgery to both sides of the thigh. Bilateral thigh abscesses were drained and radical debridement was performed in the same session with surgery for the fistula. Pathological examination of the surgical specimens showed no evidence of cancer and the patient was discharged on the 14th postoperative day with complete resolution of the infection. Hip abscesses are rare, delays in the diagnosis and treatment of the underlying cause in cases of abscess secondary to abdominal or pelvic pathologies lead to an increase in mortality. Therefore, it should be kept in mind that thigh abscesses may be another side of the coin besides being seen as an isolated infection.
Keywords: Enterocutaneous fistula; Thigh abscess; Bilateral; Silent clinic